Pemberdayaan Remaja Melalui Pendidikan dan Pelatihan GenRe untuk Pendewasaan Usia Perkawinan dan Pencegahan Stunting - Dewi Susanti; Muhammad Faisal; Elda Yusefni; Erwani (CV. CENDIKIA JENIUS INDONESIA, 2025)
Adolescents constitute the largest population group in Indonesia and hold a strategic role in national development. However, high rates of early marriage and stunting indicate low readiness for transitioning into adulthood. This community service research aims to empower adolescents through the Generasi Berencana (GenRe) education and training program to promote marriage maturity and prevent stunting in Nanggalo District, Padang City. The study employed a Participatory Action Research (PAR) approach including education, training, GenRe Ambassador selection, work program development, and monitoring and evaluation. Results showed a 35% increase in adolescents' knowledge and the establishment of a GenRe Forum and 12 active youth change agents. Outputs include mass media publications, an accredited national journal article, video documentation, and an ISBN-registered handbook. In conclusion, the program effectively enhanced adolescents' capacity as agents of change in preventing early marriage and stunting.